The institution of the permanent court guardian 1919 – 1929 - Szymków, Krzysztof (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The institution of the permanent court guardian is a part of the history of the Polish probation system, which is an integral part of juvenile courts. The decree of the Chief of State Józef Piłsudski from 7 February 1919 setting up juvenile courts ought to be considered the beginning of the probation system. The institution of the permanent court guardian functioned in the period between 1919 and 1929, more precisely set forth in the abovementioned decree of the Chief of State as well as the ordinance of the Minister of Justice from 25 June 1929, which transformed the institution of the court guardian into the probation officer by the municipal and juvenile courts. The fact that at the very beginning of independent Poland the matter of the juvenile judiciary was regulated by setting up juvenile courts as well as the institution of the permanent court guardian only testifies to the seriousness of the problem that the young country had to face. The aim of the article is to present the legal basis, scope of responsibilities as well as the functioning of permanent court guardians. The institution of the permanent court guardians marked the beginning of the Polish probationary system and the modern juvenile courts based mostly on adopting educational measures in treating juvenile delinquents.
Keywords: permanent court guardians; probation system; juvenile courts